A Kitchen, the Twitter and My Friends: Having a Coffee with ICT - Anacleto, Junia; Bueno, Andre; Ferreira, Vinicius (Anais do Workshop sobre Aspectos da Interação Humano-Computador na Web Social (WAIHCWS), 2017)
As Information and Communication Technologies (ICTs) permeate people's interactions, designers face the challenge of creating new forms to promote contact among unrelated individuals and fostering the communication and potential support to leverage the sense of community in public spaces. This work is related to Urban Computing, studying the correlation among people, urban spaces and technologies. Our research is about observing and understanding the impact of ICT social support in a physical and social context. We developed an interactive application aiming at leveraging socialization in a public space inside a University Campus. Using an in-the-wild approach, our system brings some evidences showing to be efficient in supporting ways for people to socialize in situ and remotely.